2021
DOI: 10.1021/acs.biomac.1c01372
|View full text |Cite
|
Sign up to set email alerts
|

Development of Icephilic ACTIVE Glycopeptides for Cryopreservation of Human Erythrocytes

Abstract: Ice formation and recrystallization exert severe impairments to cellular cryopreservation. In light of cell-damaging washing procedures in the current glycerol approach, many researches have been devoted to the development of biocompatible cryoprotectants for optimal bioprotection of human erythrocytes. Herein, we develop a novel ACTIVE glycopeptide of saccharide-grafted ε-poly­(L-lysine), that can be credited with adsorption on membrane surfaces, cryopreservation with trehalose, and icephilicity for validity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 83 publications
0
48
0
Order By: Relevance
“…Then the concentrated RBCs were lysed in DI water for the measurement of trehalose content ( c s , mg mL −1 ), or re-suspended in PBS in parallel to determine the RBC concentration (RBC, ×10 12 L −1 ) and mean corpuscular volume (MCV, ×10 −15 L) using an automated hematology analyzer (Bowlinman BM830, Beijing, China). 29 Samples incubated with 900 mOsm L −1 PBS were treated as blank ( c 0 , mg mL −1 ). The trehalose content was calculated according to the following eqn (2): 13,17,28,29,46 where 342.3 (g mol −1 ) refers to the molecular weight of trehalose and 0.7 belongs to the hRBC volume index.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then the concentrated RBCs were lysed in DI water for the measurement of trehalose content ( c s , mg mL −1 ), or re-suspended in PBS in parallel to determine the RBC concentration (RBC, ×10 12 L −1 ) and mean corpuscular volume (MCV, ×10 −15 L) using an automated hematology analyzer (Bowlinman BM830, Beijing, China). 29 Samples incubated with 900 mOsm L −1 PBS were treated as blank ( c 0 , mg mL −1 ). The trehalose content was calculated according to the following eqn (2): 13,17,28,29,46 where 342.3 (g mol −1 ) refers to the molecular weight of trehalose and 0.7 belongs to the hRBC volume index.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…29 Samples incubated with 900 mOsm L À1 PBS were treated as blank (c 0 , mg mL À1 ). The trehalose content was calculated according to the following eqn (2): 13,17,28,29,46 Intracellular trehalose mM…”
Section: Trehalose Loadingmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Our previous studies demonstrated that membranedisruptive activity could be improved by phenethylamine-grafted g-poly(glutamic acid) or hydrophobic phenylalanine and lysine modified poly(aspartic acid), 18,32 while trehalose-functional and saccharide-grafted glycopeptides based on e-PL could enhance glycerol-free cryopreservation of sRBCs and hRBCs, respectively. 33,34 Based on the above achievements, in this work, we tried to synthesize new cationic polymers that could self-assemble into nanoparticles to interact with hRBC membranes. Thus, e-PL was coupled with different alkyl carboxylic acids to obtain amphipathic polymers with hydrophobic side groups, which were expected to be good candidates for delivery of trehalose into hRBCs.…”
Section: Introductionmentioning
confidence: 99%